An exact solution for geophysical edge waves in the f-plane approximation. (August 2015) - Ionescu-Kruse, Delia
Abstract: We propose an exact implicit solution to the nonlinear geophysical edge-wave problem in the f -plane approximation. Adequate for this exact solution is the Lagrangian framework. We confirm that this solution is an example of a trapped wave.